Quick design tool for welded circular hollow sections joint using MS Excel - Law, Xiao Han. (2009)
Steel structures have been increasingly recommended and common in the construction industry due to its features and advantages. One of the advantages is the provision for larger clear span as the strength is higher than concrete and therefore more flexibility with the designing of the structural layouts. Besides, steel structures cuts down the amount of time required for construction due to its fast production and erection from the factory and on to site. This in turn reduces the amount of time for completion for construction, allowing the structure to have a faster completion for projects. Steel, providing high sustainability criteria, enable the material to be reused when demolished. With the increasing use of steel structures, hand calculations are commonly used to analyze and check the adequacy and the efficiency of the joint connections. However, it can be uneconomic and time consuming when there is more than one joint connection to design. Therefore, with the aid of CHS spreadsheet, designing and analyzing of the joint connections would be much faster, efficient and eliminates the possibility of calculation errors by hand calculation. The aim of this project is to develop a user-friendly spreadsheet for analyzing of welded circular hollow section connections, to assist the user in achieving the required end result for evaluations quickly.